2022
DOI: 10.3390/ijms23179894
|View full text |Cite
|
Sign up to set email alerts
|

T-Type Calcium Channels: A Mixed Blessing

Abstract: The role of T-type calcium channels is well established in excitable cells, where they preside over action potential generation, automaticity, and firing. They also contribute to intracellular calcium signaling, cell cycle progression, and cell fate; and, in this sense, they emerge as key regulators also in non-excitable cells. In particular, their expression may be considered a prognostic factor in cancer. Almost all cancer cells express T-type calcium channels to the point that it has been considered a pharm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 137 publications
(150 reference statements)
0
4
0
Order By: Relevance
“…We are of the opinion that the dephosphorylation of Cav3.2, in conjunction with its phosphorylation by CaMKII or potentially other kinases, plays a crucial role in maintaining the functional homeostasis of Cav3.2. This is particularly significant considering its involvement in conditions such as chronic pain, autism, epilepsy, and primary aldosteronism [4,5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We are of the opinion that the dephosphorylation of Cav3.2, in conjunction with its phosphorylation by CaMKII or potentially other kinases, plays a crucial role in maintaining the functional homeostasis of Cav3.2. This is particularly significant considering its involvement in conditions such as chronic pain, autism, epilepsy, and primary aldosteronism [4,5].…”
Section: Discussionmentioning
confidence: 99%
“…The low-voltage-activated calcium channels, known as T-type (T for transient or tiny) channels, exhibit rapid inactivation kinetics and are capable of opening near the resting membrane potential, contributing to membrane depolarization. Vertebrates express three different T-type calcium channels: Cav3.1, Cav3.2, and Cav3.3 [3,4]. Dysfunctions in T-type calcium channels are linked to various disease conditions, including epilepsy, autism, neuromuscular disorders, and chronic pain [5].…”
Section: Introductionmentioning
confidence: 99%
“…TTCC is found in large numbers only in sinus pacemaker cells and Purkinje fibers of many species in the adult heart and is vital for maintaining pacemaker activity. 29 Furthermore, in the presence of iron overload, Kumfu et al 30 showed that the TTCC blocker nifedipine or efonidipine blocked iron uptake. Although non-selective TTCC blockers can also block LTCC, they block TTCC more effectively than LTCC.…”
Section: Calcium Handling Ion Channels Iron Disturbancementioning
confidence: 99%
“…Besides LTCC, T‐type Ca 2+ channels (TTCC) is also related to Iron metabolism. TTCC is found in large numbers only in sinus pacemaker cells and Purkinje fibers of many species in the adult heart and is vital for maintaining pacemaker activity 29 . Furthermore, in the presence of iron overload, Kumfu et al 30 .…”
Section: Calcium Handling Ion Channels Iron Disturbancementioning
confidence: 99%